Elucidating Complex Queries Based on Curtailing Technique for Effective Green Communication - et. al., Anshy Singh, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A system has been developed to improve on the quality of search for which we have replaced the present searching methods by our procedure Explore Scheme, which greatly increases the utility of Web, over what is available today. None of the Search Techniques is able to deal effectively and efficiently with the huge volume of information posted on World Wide Web. In the current searching methodology, our proposed system emphasizes on enhancing the searching method by our proposed Explore-Scheme procedure, which provides solution to the complex queries based on contextual expansion. It is our observation that in investigating relevance feedback questions (both existing and new), we will implement the Explore-Scheme algorithm on web in this way we can enhance the ability which will give rise to the information which is good, of some use and relevant. Currently, we are implementing the system that is able to demonstrate important properties of the presented approach. Our method reduces the word to its atomic part thus curtailing the size of the dictionary by saving Storage space and processing time enhancing the processing speed of query. We can finally say that our proposed algorithm will definitely improve the information retrieval capabilities and are able to deal effectively and efficiently with the huge volume of information posted on World Wide Web.